The Validity of Imam Shafi‘i, Criticism, and the Influence of Yahya Bin Ma’in's Accusations on the Weakness of Transmission in Hadith Chains - Mas Hasan Rifqi; Amaliyah Widya Mahanani; Afro’ Anzali Nurizzati Arifah (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Imam Shafi‘i is widely recognized as a leading mujtahid and a major authority in Islamic jurisprudence and hadith scholarship, whose narrations have long been referenced in classical Islamic sciences. Specific Background: Despite this recognition, certain criticisms—most notably attributed to Yahya bin Ma‘in—questioned Imam Shafi‘i’s reliability as a hadith transmitter, particularly regarding sanad assessment within the tradition of jarh wa ta‘dil. Knowledge Gap: These accusations have often been cited without systematic evaluation against broader scholarly consensus and established methodological principles of hadith criticism. Aims: This study aims to reassess Yahya bin Ma‘in’s accusations and examine their standing within jarh wa ta‘dil, focusing on whether they undermine Imam Shafi‘i’s status as a thiqah narrator. Results: Based on qualitative library research and comparative analysis of classical sources, the study finds that the accusations lack substantiated grounds, are contradicted by other authenticated statements from Yahya bin Ma‘in himself, and are outweighed by extensive scholarly endorsement of Imam Shafi‘i’s reliability. Novelty: The article provides a structured clarification that situates isolated criticism within the wider epistemological framework of hadith sciences, emphasizing scholarly consensus and narrator reputation. Implications: These findings reaffirm Imam Shafi‘i’s authority in hadith transmission and offer a methodological reference for addressing contested evaluations of narrators in Islamic scholarship. Highlights: Accusations against Imam Shafi‘i lack methodological consistency when examined through classical hadith principles. Scholarly consensus affirms his status as a trustworthy narrator despite isolated critiques. Omission from certain canonical compilations does not constitute evidence of unreliability. Keywords: Imam Shafi‘I, Hadith Transmission, Jarh wa Ta‘dil, Sanad Criticism, Yahya bin Ma‘in